Protecting the Existence of Pancasila and Its Implementation in Society in the Era Towards 5.0 - Rizka Adilla Octavia; Ellena Syane Fransisca; Imam Tauhid Ragananda; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
As the basis of the state, Pancasila is used as the basis for building the Unitary State of the Republic of Indonesia. Unavoidable globalization seems to make all aspects unlimited. This needs to be balanced with the implementation of Pancasila in social life so that it maintains its existence.